Continuous weeklong measurements of indoor particle levels in a Minnesota Tribal Casino Resort - Zheng Zhou; David Bohac; Raymond G. Boyle (BMC, 2016)
Abstract Background Secondhand smoke (SHS) exposure for workers and patrons in hospitality venues is a persistent and significant public health concern. We designed this study to provide a comprehensive assessment of SHS exposure inside an Indian Tribal Casino in Minnesota. Methods Real-time fine particulate matter (PM2.5) concentrations were measured at multiple locations for up to 7 days. The field monitoring provided information on the day of week and time of day variation of SHS exposure, as well as comparisons between smoking and non-smoking areas. Results Indoor PM2.5 level was nearly 13 times the concurrent outdoor PM2.5 level. Gaming floor hourly PM2.5 level was highest on Saturday night, averaged at 62.9 μg/m3. Highest PM2.5 concentration was observed in smoking-permitted employee break room, reaching 600 μg/m3. PM2.5 readings in non-smoking sections exhibited same temporal pattern as the readings in smoking sections. Conclusions The results show that indoor concentration of PM2.5 is substantially higher than the outdoor level, posing health risks to casino workers and patrons. SHS can migrate into adjacent non-smoking areas very quickly. The casino's ventilation system did not fully eliminate SHS. A completely smoke-free casino would be the only way to fully protect non-smoking patrons and employees from the dangers of tobacco smoke.